Epigenetic Control of IFN-γ Host Responses During Infection With Toxoplasma gondii - Nast, Roswitha; Choepak, Tenzin; Lüder, Carsten G. K. (Frontiers in Immunology, 2020)
Host defense against the human pathogen Toxoplasma gondii depends on secretion of interferon (IFN)-γ and subsequent activation of monocytic cells to combat intracellular parasites. Previous studies have shown that T. gondii evades IFN-γ-mediated immunity by secreting the effector TgIST into the host cell where it binds to STAT1, strengthens its DNA binding activity and recruits the Mi-2/NuRD complex to STAT1-responsive promoters. Here we investigated the impact of the host chromatin environment on parasite interference with IFN-γ-induced gene expression. Luciferase reporters under control of primary and secondary IFN-γ response promoters were only inhibited by T. gondii when they were stably integrated into the host genome but not when expressed from a plasmid vector. Absence of CpG islands upstream and/or downstream of the transcriptional start site allowed more vigorous up-regulation by IFN-γ as compared to CpG-rich promoters. Remarkably, it also favored parasite interference with IFN-γ-induced gene expression indicating that nucleosome occupancy at IFN-γ-responsive promoters is important. Promoter DNA of IFN-γ-responsive genes remained largely non-methylated in T. gondii-infected cells, and inhibition of DNA methylation did not impact parasite interference with host responses. IFN-γ up-regulated histone marks H4ac, H3K9ac and H3K4me3 but down-regulated H3S10p at primary and secondary response promoters. Infection with T. gondii abolished histone modification, whereas total nuclear activities of histone acetyl transferases and histone deacetylases were not altered. Taken together, our study reveals a critical impact of the host chromatin landscape at IFN-γ-activated promoters on their inhibition by T. gondii with a comprehensive blockade of histone modifications at parasite-inactivated promoters.